2019
DOI: 10.1177/000313481908501232
|View full text |Cite
|
Sign up to set email alerts
|

Rising BMI is Associated with Increased Rate of Clinically Relevant Pancreatic Fistula after Distal Pancreatectomy for Pancreatic Adenocarcinoma

Abstract: Clinically relevant pancreatic fistula (CR-POPF), after distal pancreatectomy (DP), remains a clinical challenge. Prior studies investigating the relationship between BMI and CR-POPF have yielded conflicting results. We hypothesized that BMI is associated with CR-POPF in patients having DP for pancreatic ductal adenocarcinoma (PDAC). Patients who underwent DP for PDAC at a single institution from 2006 to 2018 were retrospectively reviewed. A CR-POPF was defined as International Study Group of Pancreatic Surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 26 publications
0
24
2
Order By: Relevance
“…The previously reported representative risk factors for POPF after DP include obesity, younger age, malnutrition, and soft pancreas [2][3][4][5], but many reports have indicated that pancreatic thickness is the most important risk factor [17]. Univariate analysis in the present study showed that, among the abovementioned factors, high BMI (obesity), younger age, and pancreatic thickness were detected as risk factors, and multivariate analysis showed that high BMI (obesity) and pancreatic thickness were detected as independent risk factors; these results are similar to those in previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously reported representative risk factors for POPF after DP include obesity, younger age, malnutrition, and soft pancreas [2][3][4][5], but many reports have indicated that pancreatic thickness is the most important risk factor [17]. Univariate analysis in the present study showed that, among the abovementioned factors, high BMI (obesity), younger age, and pancreatic thickness were detected as risk factors, and multivariate analysis showed that high BMI (obesity) and pancreatic thickness were detected as independent risk factors; these results are similar to those in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…There is a higher incidence of postoperative pancreatic stula (POPF) after distal pancreatectomy (DP) than thatafter pancreaticoduodenectomy (PD) [1];POPFisthe most clinically problematic complication of these procedures. Various risk factors for POPF after DP have been reportedthus far, including obesity, younger age, malnutrition, pancreatic thickness,and soft pancreatic texture (i.e.,soft pancreas) [2][3][4][5]. Althoughmost of these factors can beevaluated preoperatively, pancreatictexturecan be determined only by intraoperative ndings.…”
Section: Introductionmentioning
confidence: 99%
“…The previously reported representative risk factors for POPF after DP include obesity, younger age, malnutrition, and soft pancreas [ 10 13 ], but many reports have indicated that pancreatic thickness is the most important risk factor [ 26 ]. As the global population ages, the demand for pancreatic surgery in elderly patients has increased [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a higher incidence of POPF after DP than that after PD [ 9 ]. Various risk factors for POPF after DP have been reported thus far, including obesity, younger age, malnutrition, pancreatic thickness, and soft pancreatic texture (i.e., soft pancreas) [ 10 13 ]. Although most of these factors can be evaluated preoperatively, pancreatic texture can be determined only by intraoperative findings.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity is perceived to be a risk factor for intraoperative and postoperative incidents 15. Elevated POPF rates have been observed in obese patients, compared with patients who have normal BMI, after pancreatic surgery 16. Increased fatty infiltration is considered to be responsible for increased risk of POPF, to some extent 17.…”
Section: Discussionmentioning
confidence: 99%